Experiences of nurse educators facilitating and teaching in an international setting. Issue 1 (14th December 2021) - Richter, Solina; Sullivan, Ginger; Urindwanayo, Desire; Kelly, Isabelle
Abstract: Background: Multiple studies focus on the experiences of visiting students from high resource regions that participated in clinical placements in lower resource countries but less focus on the experiences of the educators accompanying students. Aim: The purpose of this study was to explore the experiences of educators during an international clinical placement of nursing students in a country in West Africa. Methods: We implemented a focussed ethnographic design. We purposively sampled educators who accompanied students on an international clinical placement. Data collection from 2018 to 2019 consisted of in‐depth individual interviews. We utilized Roper and Shapira's (2000, 10.4135/9781483328294.) data analysis process, which includes coding keywords, identifying patterns and theorizing. Findings: Three themes emerged from the data: rewards in accompanying students, challenges experienced and the need for mentoring and continuous support. Educators found it rewarding to see growth in students, how students developed as global citizens, how students developed critical thinking and problem‐solving skills and create lifelong friendships. Conclusion: Educators who accompany nursing students to international clinical placement experience valuable learning and challenging issues. Educators must navigate, support and advance student learning when on an international placement. It is crucial to have adequate institutional support from both the home and host country. Abstract : Summary statement: What is already known about this topic? Multiple research studies focus on the experiences of visiting students from high resource regions that participated in clinical placements in lower resource countries but less focus on the experiences of the educators accompanying students. Multiple rewards exist for educators who accompanying students on an international clinical placement. Nurse educators are expected to mentor students and provide continuous support. What this paper adds? The need for continuous contact between the educators and the home faculty is highlighted. Mentoring topics to 'soften' the impact of the challenges experiences by educators are identified; this includes regular debriefing with senior educators at the home and host university. The importance of working with the host during the predeparture period, as well as report on arrival and have regular meetings during the placement to ensure that both the needs of the visiting student group and the host are met, is highlighted. The implications of this paper: (how findings influence or can be used to change policy/practice/research/education) A well‐developed support system and debriefing sessions are necessary for the accompanying faculty member. Research is needed to develop the content of a mentorship model/framework for junior academics that plan to accompany students on international clinical placements to low and middle‐income countries. Additional research is needed on the value of pairing a junior academic with an experienced mentor to answer questions as they arise related to day‐to‐day challenges and student related questions during the international clinical placements.